Mobile snapshot hyperspectral imaging device for skin evaluation using diffractive optical elements. Issue 4 (28th January 2021) - Kern, Christian; Speck, Uwe; Riesenberg, Rainer; Reble, Carina; Khazaka, Georg; Zieger, Michael; Kaatz, Martin; De Gregorio, Marco; Fischer, Frank
Abstract: Objective: A mobile handheld snapshot hyperspectral imaging device was developed and tested for in vivo skin evaluation using a new spectral imaging technology. Methods: The device is equipped with four different LED light sources (VIS, 810 nm, 850 nm, and 940 nm) for illumination. Based on a diffractive optical element (DOE) combined with a CMOS sensor chip, a snapshot hyperspectral imager is achieved for the application on human skin. The diffractive optical element (DOE) consists of a two‐dimensional array of identically repeated diffractive microstructures. One hyperspectral image for all wavelength regions is taken within a few seconds. Complex recalculation of the VIS spectral distribution and image information from the received DOE image requires several minutes, depending on computing performance. A risk assessment on the irradiation sources shows no risk of harm due to the LED radiation. Results: Skin tone color patches experiments reproducibly deliver images and spectra of different skin tones. First i n vivo use of the device identified pigmentation changes within the field of view. Conclusion: We present a working mobile snapshot hyperspectral imaging tool based on diffractive optical elements. This device or future developments thereof can be used for broad skin evaluation in vivo.